Next-Generation Sequencing Accelerates Crop Gene Discovery - Nguyen, Khanh Le; Grondin, Alexandre; Courtois, Brigitte; Gantet, Pascal (Trends in plant science, 2019)
The identification and isolation of genes underlying quantitative trait loci (QTLs) associated with agronomic traits in crops have been recently accelerated thanks to next-generation sequencing (NGS)-based technologies combined with plant genetics. With NGS, various revisited genetic approaches, which benefited from higher marker density, have been elaborated. These approaches improved resolution in QTL position and assisted in determining functional causative variations in genes. Examples of QTLs/genes associated with agronomic traits in crops and identified using different strategies based on whole-genome sequencing (WGS)/whole-genome resequencing (WGR) or RNA-seq are presented and discussed in this review. More specifically, we summarize and illustrate how NGS boosted bulk-segregant analysis (BSA), expression profiling, and the construction of polymorphism databases to facilitate the detection of QTLs and causative genes.
Keywords: quantitative trait loci; vysoce účinné nukleotidové sekvenování; crops; Phenotype; genetics; next-generation sequencing; bulk-segregant analysis; lokus kvantitativního znaku; genetické asociační studie; Genetic Association Studies; mapování chromozomů; jednonukleotidový polymorfismus; candidate gene; fenotyp; High-Throughput Nucleotide Sequencing; Quantitative Trait Loci; Polymorphism, Single Nucleotide; Chromosome Mapping